IMPROVING THE LEARNING OF WATER ABLUTION TREATMENT THROUGH IPAL JAILANGKUNG IN 6TH GRADE OF SDN DINOYO 1 - Aminin, Istiqomah (Proceedings of the International Conference on Green Technology; Vol 9 No 1 (2018): Proceeding of the 9th International Conference on Green Technology 2018, 2019)
The availability of clean water is one of the important issues of sustainable development goals defined by the Board of the United Nations. The condition was the availability of clean water was currently starting to concern. In support of the sustainable development goals to keep the availability of clean water, then do an innovation learning that using wudu wastewater become aquaponics to kangkung plant and pool water of catfish or IPAL JAILANGKUNG. The purpose of this research was to describe the used of IPAL JAILANGKUNG in improving wastewater treatment learning former wudu. This research method using classroom action research developed by Kemmis and McTaggart. The subject of this research was 6th grade of SDN Dinoyo 1. Data collection was done by observation, interview, anecdotal records, documentation and tests. This research was conducted in two cycles. The results showed on the final act of an increase in wudu waste water treatment learning. The result of the study reached thoroughly above 78%.